Models for the development of work-readiness skills for students in Vietnamese universities - Tran, Nghia Le Huu (Advances in Social Sciences Research Journal, 2017)
Complementing existing literature about how to develop generic skills (GS) for students effectively, this article will report on models that six Vietnamese universities developed to train students in GS. It will also analyse factors influencing the development of these models and discuss factors contributing to the effectiveness of each of these models. Content analysis of relevant documents and 69 interviews with key informants of the implementation revealed that despite sharing a similar concept for executing GS policy, these universities translated it into practice differently, in terms of implementation scale and the channels and pedagogical practices through which GS are imparted to students. The analysis showed that curriculum autonomy, university leadership, and connection with external stakeholders were pivotal for the adoption of these GS implementation models. It also indicated that institutional leadership that is capable of engaging stakeholders was key for the success of using these GS implementation models.